Factors Affecting Users’ Mental Models of a Web Search Engine: A Case Study - Ping, Li; Beheshti., Jamshid (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Focusing on doctoral students as a specific user group, for a case study, this research investigates factors that might affect users’ mental models of a Web search engine measured in the dimension of completeness, and subsequently on their search performance. Data collection techniques include interview, observation and four standard tests. Se basant sur les étudiants au doctorat comme groupe spécifique d’utilisateurs pour réaliser une étude de cas, cette recherche examine les facteurs pouvant affecter les modèles mentaux des utilisateurs d’un moteur de recherche web, mesurés en termes d’exhaustivité, et subséquemment en termes de performance de recherche. Les techniques de collecte de données incluent l’entrevue, l’observation et quatre tests standardisés.